Prospects for the digital transformation of the transport industry - O. B. Repkina (Путеводитель предпринимателя, 2024)
The article discusses the problems and prospects of digitalization of the transport industry. The policy of modernization, introduction of advanced automated systems and highly automated vehicles is consistently implemented here. Having identified the main digital technologies used in transport activities, the problems and threats associated with digital transformation are considered. Having analyzed the conceptual framework and features of the legal regulation of the regulatory framework, conclusions are drawn about the lack of a single approach and uniformity both in terminology and in the mechanism of regulation. Special attention is paid to the issues of regulation of the information space that arise in the process of ensuring the safety of the functioning of the transport infrastructure. The issue of employment, potentially arising from the spread of artificial intelligence and unmanned vehicles, is also touched upon. In order to solve urgent problems, the need for mandatory insurance of the most risky elements of the transport system is justified, which is still an omission. In conclusion, it is noted that due to the urgency and inevitability of the digitalization process in all areas of society and, in particular, the transport industry, it is necessary not only to keep up with current trends, but also, first of all, to create conditions that meet the needs of the effective functioning of the system itself.